Farm automation system with IoT application - Hasan, Mahmudul; Hossain, Syed Maksud; Rahman, Mohammad Saad Ur; Ullah, M. M. Sakib (BARC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.